2019
DOI: 10.1111/1467-9566.12897
|View full text |Cite
|
Sign up to set email alerts
|

A multilevel neo‐institutional analysis of infection prevention and control in English hospitals: coerced safety culture change?

Abstract: Despite committed policy, regulative and professional efforts on healthcare safety, little is known about how such macro-interventions permeate organisations and shape culture over time. Informed by neo-institutional theory, we examined how inter-organisational influences shaped safety practices and inter-subjective meanings following efforts for coerced culture change. We traced macro-influences from 2000 to 2015 in infection prevention and control (IPC). Safety perceptions and meanings were inductively analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Specifically, across qualitative methods and quantitative surveys, there were dimensions related to patient involvement in safety culture; 41 61 64-66 interpersonal dynamics around trusting colleagues, developing a shared understanding and valuing and empowering individuals; 38 60 and the need for flexibility and improvisation. 28 67 68 However, extending on the latter of these themes, qualitative and mixed methods studies also reported a range of complexities, 67 external pressures, 69 contextual dependencies 57 and the need to manage and prioritise risks in delivering safe care to patients, 45 which were not adequately captured by the narrow scope of established themes, such as 'resources and constraints'.…”
Section: Themes For Safety Culture Dimensionsmentioning
confidence: 99%
“…Specifically, across qualitative methods and quantitative surveys, there were dimensions related to patient involvement in safety culture; 41 61 64-66 interpersonal dynamics around trusting colleagues, developing a shared understanding and valuing and empowering individuals; 38 60 and the need for flexibility and improvisation. 28 67 68 However, extending on the latter of these themes, qualitative and mixed methods studies also reported a range of complexities, 67 external pressures, 69 contextual dependencies 57 and the need to manage and prioritise risks in delivering safe care to patients, 45 which were not adequately captured by the narrow scope of established themes, such as 'resources and constraints'.…”
Section: Themes For Safety Culture Dimensionsmentioning
confidence: 99%
“…However, as a profession, nurses can also play a central role in the improvement of prevention and control (IPC) of bacterial infections (Kyratsis et al, 2019). Studies argue that nursing perspectives, active participation of nurses and organised clinical practice are crucial to both IPC, and to strategies to reduce AMR development and to gain optimal success of antibiotic stewardship programs across the entire spectrum of healthcare systems (Manning et al, 2016;Olans et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, studies show that access to training and educational resources on AMR for healthcare professionals increase the frequency and level of thoroughness of trained practices, which aim to minimise the spread of AMR by professionals (Chun et al., 2015 ; van Katwyk et al., 2018 ). Kyratsis et al ( 2019 ) also show that nurses are key actors for the fostering of an organisational safety culture among other healthcare professionals. Manning et al ( 2016 ) argue that it is important to act through various nursing organisations and constituencies because of the dire consequences of AMR together with the urgency of engaging the entire nursing community in both changing the way clinicians and consumers use antibiotics, including the overall reduction of consumed antibiotics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a paucity of knowledge on why certain interventions appear to be more effective than others in influencing prescribing behaviour, and how interventions work in synergy or in opposition to influence prescribing behaviour. An analysis of factors influencing prescribing behaviour, their interaction and the magnitude of the effects produced by these interactions is critical in order to inform the selection of policy alternatives and to shape an optimal "mix" of policy interventions (Kyratsis et al, 2019).…”
Section: Factors Influencing Antibiotic Prescribing: Literature Reviewmentioning
confidence: 99%